2012
DOI: 10.1523/jneurosci.5177-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5/p25-Induced Cytosolic PLA2-Mediated Lysophosphatidylcholine Production Regulates Neuroinflammation and Triggers Neurodegeneration

Abstract: The deregulation of cyclin-dependent kinase 5 (Cdk5) by p25 has been shown to contribute to the pathogenesis in a number of neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), Parkinson's disease (PD) and Alzheimer's disease (AD). In particular, p25/Cdk5 has been shown to produce hyperphosphorylated tau, neurofibrillary tangles as well as aberrant amyloid precursor protein processing found in AD. Neuroinflammation has been observed alongside the pathogenic process in these neurodegenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 60 publications
(61 reference statements)
2
105
0
2
Order By: Relevance
“…Phospholipase A2 (PLA2) converts erythrocyte PC and PS into lysophospholipids that readily leave the membrane to function as regulatory messengers 39. Lyso‐PC released from glial cells initiate neurodegenerative processes through inflammatory cascades 40. Likewise, activated platelets, a common feature in CAD, catalyze the deacylation of PS into lyso‐PS 41.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase A2 (PLA2) converts erythrocyte PC and PS into lysophospholipids that readily leave the membrane to function as regulatory messengers 39. Lyso‐PC released from glial cells initiate neurodegenerative processes through inflammatory cascades 40. Likewise, activated platelets, a common feature in CAD, catalyze the deacylation of PS into lyso‐PS 41.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, in this transgenic, up regulation of p25 and hyperactivity of Cdk5 initiate inflammation via phosphorylation and activation of neuronal phospholipase 2A followed by astroglyosis and microgliosis which precede Abeta accumulation and tau phosphorylation [19]. In fact the situation has become even more confounding with the mixed results from other p25 mouse transgenic initiated at fertilization [22,23].…”
Section: Intraperitoneal (Ip) Injection Paradigmmentioning
confidence: 93%
“…In the earlier study most data were reported after 5-12 weeks of induction and showed upregulation of Cdk5/p25 activity correlated with tau phosphorylated aggregates, a neurofibrillary pathology [17]. A later study recorded earlier time points with Cdk5 activation evident after one week induction [19]. Virtually at the same time, inflammatory signs were seen with an uptick of GFAP at one week, cytokines and chemokines of microgliosis and phosphor-tau after 4 weeks induction, followed by Abeta, most evident at 8 weeks post induction.…”
Section: Proof Of Concept; the Ck-tgp25 Transgenicmentioning
confidence: 94%
See 2 more Smart Citations